Provenance Trial of Pinus caribaea in Koraput, Orissa (India) - Swain, D.; Patnaik, T. (Indian Forester, 1996)
Result on seed germination, height growth, diameter growth and survival percentage are presented from a provenance trial (1983) at Koraput Research Station, Orissa with Pinus caribaea at the age of 10 years. A total number of 20 provenance i.e. 16 ofvar-hondurensis, 2 ofvar-bahamensis and 2 of var-caribaea are taken into account. Following an analysis of the above parameters, it is found that Prov-Santa Clara, Nicaragua of the var-hondurensis shows relatively better performance than rest of the provenances where as Prov-Cuba of the var-caribaea shows a poor result in comparison to other provenances.